THE TRADEMARK RENEWAL PROCESS RELATES TO THE EXCLUSIVE RIGHTS OF THE BRAND HOLDER BASED ON LEGAL CERTAINTY - Laiya, Leonard Tasuno; Rahaditya (Awang Long Law Review, 2023)
In this age of digitalization, the significance of Intellectual Property cannot be ignored. In experiencing the changing era, the Intellectual Property protection system also needs to adjust well, along with the changes, growth, challenges, and opportunities that exist. The growth of the era cannot be ignored, and in the context of the current growth of Intellectual Property, the protection system must also explore so as not to lag behind and protect the rights of individuals efficiently. With this growth, the process of acquisition and ownership of Intellectual Property as a form of protection of intellectual property, absolutely must be supported, facilitated and facilitated by all parties. With such support, facilitation, and ease, this will not only increase the number and quality of Intellectual Property ownership, but more importantly, it will reflect progress in the field of science and technology at the national level. Not only that, it is also a sign of economic progress and the welfare of citizens. The most important is the trademark which is one of and cannot be separated by aspects of Intellectual Property, along with the Exclusive Rights of the Trademark Holder. Because all of these contexts concern the principle of legal certainty. In the context of the disappearance of national borders due to globalization, with the presence of freedom of entry of objects and services. The management of intellectual property rights is very meaningful for the nation's materials because it can share legal protection for intellectual property owned by creators, inventors, designers, and creators related to their creations or intellectual works.